RETRACTED: Baricitinib protects mice from sepsis-induced cardiac dysfunction and multiple-organ failure - Verra, Chiara; Mohammad, Shireen; Alves, Gustavo Ferreira; Porchietto, Elisa; Coldewey, Sina Maren; Collino, Massimo; Thiemermann, Christoph (Frontiers in Immunology, 2023)
Sepsis is one of the major complications of surgery resulting in high morbidity and mortality, but there are no specific therapies for sepsis-induced organ dysfunction. Data obtained under Gene Expression Omnibus accession GSE131761 were re-analyzed and showed an increased gene expression of Janus Kinase 2 (JAK2) and Signal Transducer and Activator of Transcription 3 (STAT3) in the whole blood of post-operative septic patients. Based on these results, we hypothesized that JAK/STAT activation may contribute to the pathophysiology of septic shock and, hence, investigated the effects of baricitinib (JAK1/JAK2 inhibitor) on sepsis-induced cardiac dysfunction and multiple-organ failure (MOF). In a mouse model of post-trauma sepsis induced by midline laparotomy and cecal ligation and puncture (CLP), 10-week-old male (n=32) and female (n=32) C57BL/6 mice received baricitinib (1mg/kg; i.p.) or vehicle at 1h or 3h postsurgery. Cardiac function was assessed at 24h post-CLP by echocardiography in vivo, and the degree of MOF was analyzed by determination of biomarkers in the serum. The potential mechanism underlying both the cardiac dysfunction and the effect of baricitinib was analyzed by western blot analysis in the heart. Trauma and subsequent sepsis significantly depressed the cardiac function and induced multiple-organ failure, associated with an increase in the activation of JAK2/STAT3, NLRP3 inflammasome and NF-κβ pathways in the heart of both male and female animals. These pathways were inhibited by the administration of baricitinib post the onset of sepsis. Moreover, treatment with baricitinib at 1h or 3h post-CLP protected mice from sepsisinduced cardiac injury and multiple-organ failure. Thus, baricitinib may be repurposed for trauma-associated sepsis.